Contemporary Woman between Feminism and Tradition: Современата жена помеѓу феминизмот и традицијата - Petrova, Silvia; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2008)
Author(s): Silvia Petrova | Силвија Петрова Title (English): Contemporary Woman between Feminism and Tradition Title (Macedonian): Современата жена помеѓу феминизмот и традицијата Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 201-231 Page Count: 31 Citation (English): Silvia Petrova, “Contemporary Woman between Feminism and Tradition,” Identities: Journal for Politics, Gender and Culture, Vol. 7, No. 1-2 (Summer 2008 - Winter 2009): 201-231. Citation (Macedonian): Силвија Петрова, „Современата жена помеѓу феминизмот и традицијата“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 7, бр. 1-2 (лето 2008 - зима 2009): 201-231.